Development of molecularly imprinted polymers for the removal of levofloxacin - Rashid, Mahmood; Showkat, Ahmad Bhawani; Syed Rizwan, Shafqat; Rachel Marcella, Roland (Springer Nature, 2025)
The extensive use of antibiotics and their persistence in the environment make them emerging pollutants of global concern, posing serious risks to ecosystems and public health. Among them, the broad-spectrum fluoroquinolone antibiotic levofloxacin (LEV) is widely prescribed for bacterial infections and has frequently been detected in freshwater systems and environmental matrices. Its presence is linked to the development of antibiotic resistance and ecological toxicity, underscoring the urgent need for efficient removal strategies. In this study, levofloxacinimprinted polymers (LEV-MIPs) were developed using a precipitation polymerisation method. A set of nine LEVMIPs was synthesised using three solvent combinations: ethanol: acetonitrile, ethanol: dimethyl sulfoxide, and ethanol: carbon tetrachloride. Methacrylic acid (MAA) served as the functional monomer (1–3 mmol), ethylene glycol dimethacrylate (EGDMA) as the cross-linker (16 mmol), and azobisisobutyronitrile (AIBN) as the initiator (0.1 mmol). Among them, two formulations (LEV3-MIP and LEV6-MIP) demonstrated superior removal efficiency. Structural and thermal characterisation by FTIR, SEM/EDX, and TGA confirmed successful polymer synthesis, with surface analysis revealing spherical, monodispersed particles of ~1.5 μm. Batch adsorption assays showed removal efficiencies of 97.85% (LEV3-MIP) and 99.15% (LEV6-MIP) under optimised conditions (15 ppm initial concentration, 0.3 mg dosage, pH 7, and 90 min and 60 min contact time, respectively). Both polymers exhibited high imprinting factors (3.081 and 3.359) and excellent reusability, with minimal efficiency loss of only 2.7% and 2.09% after ten adsorption–desorption cycles. These results highlight the strong potential of LEV-MIPs as cost-effective, selective, and reusable materials for mitigating antibiotic pollution